2016
DOI: 10.1007/s12594-016-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Analytical Evaluation of Groundwater Quality of Tirupati Area, Chittoor District, Andhra Pradesh, South India

Abstract: The multivariate statistical analysis, hydrogeochemical modelling using visual MINTEQ software, indices of base exchange and Gibbs ratio were simultaneously applied to groundwater hydrochemical data of the Tirupati area. These techniques were applied to know the principal processes controlling the water chemistry. Fifty groundwater samples were analyzed for pH, electrical conductivity (EC), Ca, Mg, Na, K, HCO3, CO3, Cl, and SO4. The results showed that the abundance of the major ions in the water samples is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The piper diagram can predict water types based on the anions into three: the sulfate type, bicarbonate and chloride type. The bicarbonate type is considered to be suitable for both drinking and agriculture practices, while the sulfate type is unsuitable for irrigation (Nagaraju et al 2016;Ziani et al 2017). All the water samples fall under bicarbonate or freshwater zone.…”
Section: Hydrogeochemical Faciesmentioning
confidence: 99%
“…The piper diagram can predict water types based on the anions into three: the sulfate type, bicarbonate and chloride type. The bicarbonate type is considered to be suitable for both drinking and agriculture practices, while the sulfate type is unsuitable for irrigation (Nagaraju et al 2016;Ziani et al 2017). All the water samples fall under bicarbonate or freshwater zone.…”
Section: Hydrogeochemical Faciesmentioning
confidence: 99%
“…− [71]. Figure 3a, b and j shows that the southern and southwestern parts of the district are characterized by lower P H value because of the presence of highly soluble salts and SO 4 − acidic ions.…”
Section: Spatial Pattern Of Groundwater Chemicalmentioning
confidence: 96%
“…The chemical components, viz. Mg, Cl, Na and SO 4 , influence rate of evaporation, recharge and anthropogenic sources of the groundwater system [6,71]. Therefore, it can be concluded that Factor 1 represents the impact of geological variation and human impact on the groundwater chemistry in the concerned area.…”
Section: Principal Component and Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh water has become a scarce commodity due to over exploitation and pollution of water. Groundwater is the most important source of water supply for drinking, agriculture, irrigation and industrial purposes (Gupta and Sunita 2009;Bhattacharya et al 2012;Li et al 2013aLi et al , 2014aNagaraju et al 2013Nagaraju et al , 2014aNagaraju et al , 2016aWu and Sun 2016). There is a growing awareness of the environmental legacy of mining activities that have been undertaken with little concern for the environment (Mahesh et al 2001;Brindha et al 2010;Tripathi et al 2011).…”
Section: Introductionmentioning
confidence: 99%